Civilising Grass : The art of the lawn on the South African Highveld - Cane, Jonathan ca. 20./21.Jh; Cane, Jonathan ca. 20./21.Jh (Book collections on Project MUSE., 2019)
Drawing on theory and conceptual tools from interdisciplinary fields such as ecocriticism, queer theory, art history and postcolonial studies, Civilising Grass offers the first sustained investigation of the lawn in Africa and contributes to the growing conversation about the complex relationships between humans and non-humans on the continent.